Entre iguales: notas sobre la socialización lingüística del alumnado inmigrado en Barcelona - Unamuno, Virginia (2011)
Barcelona, a historically bilingual city, changed its demographic profile in the past few decades due to the arrival of a large number of immigrants. In such a context, it seemed relevant to study the socialisation procedures adopted by young newcomers to take part in sociolinguistic dynamics both in the city and at school. This meant investigating how children, as new members of the host society, learn to participate in monolingual, bilingual or multilingual situations. This paper presents part of the results steaming from a research project carried out at a primary school sited in the old quarter of the city of Barcelona. It focuses on the processes of peer linguistic socialisation; that is, between children of the same age born in the city and abroad. The analysis focuses on language choices and the use of code-switching as a resource to index contextual changes (change of activity, participant, topic, etc.). Results reveal that language learning by children of immigrant origin is an imbricate process in which language development is related to the process of learning how to progressively appropriate and manage the linguistic patterns other children offer them. This socialisation process seems to be framed in the cultural expectations of both groups of children and in the social relations at the school and in the city.